Peran Komite Sekolah dalam Meningkatkan Kualitas Layanan Pendidikan - Supriadi, Agus (Program Pascasarjana Universitas Ibrahimy, 2017)
Based on kepmendiknas 044/U/2002, the school committee carries out four functions, such as giving consideration, supporter, supervisor, and mediator. The function of school committee improving the quality of educational services to the stakeholder is to do their function in school plan and educational resources. Beside that verify and ratify RKAS which is proposed by the school. The school committee’s function as the supporter is to give their thought, energy and support in extracurricular and additional lesson. The additional lessons can be done by adding extra time in English. Lesson, natural science and supporting the school budget through from student guardian to fulfill a plenty of educational infrastructures. The function of the school committee as the connector is to assist the school in creating connection an cooperation the school, the student parents and the society, guardians; organize some activates which increase awareness and society partner the last. The function of the school committee as supervisor require the students report; do evaluation of school plan and implementation in infrastructure needs, supervise the development of the school and student progress; do investigation the school funding; control the school works to look for input and suggestion from the society to increase the educational services.